Penerapan Sistem Informasi Akuntansi Pada Perusahaan Shopee - Aya Soraya; Desinta Leba; Irda Agustin Kustiwi (Akuntansi, 2024)
The Implementation of Accounting Information Systems (AIS) has become a crucial foundation for leading e-commerce companies such as Shopee in managing their financial and operational transactions. This paper explores the implementation of AIS at Shopee, outlining its benefits, challenges, and its impact on operational efficiency. Shopee integrates sophisticated accounting systems to manage transactions, inventory, and financial reporting. The use of cutting-edge technology in AIS facilitates process automation, speeds up transaction recording, and enhances data accuracy. The implementation of AIS also enables in-depth real-time analysis, providing essential insights for quick and accurate decision-making. Despite its significant benefits, the implementation of AIS is not without challenges. Managing sensitive data, ensuring information security, and regulatory compliance are crucial aspects that require careful handling. System integration also demands investment in time, resources, and employee training to maximize its potential. Overall, the implementation of AIS at Shopee has opened doors to substantial operational efficiency. Despite facing specific challenges, the use of AIS has solidified Shopee's position as an e-commerce industry leader, enabling sustained innovation, growth, and competitive advantage.